Screening for diabetic nephropathy at diabetes clinic in Su-dan - Abdul-Azim, Abdul-Azim Ali; Alawad, Awad; Younis, Faisal H. (International Journal of Health, 2014)
Background: Diabetes mellitus and its complications are one of the major health problems in Sudan. Only few patients had been screened before their complications appeared. As a result of this, many patients have not been discovered and ended with late stages of the disease, and are now showing evidence of diabetic nephropathy. Objective: The main aim of this study is at discovering the factors in terms of patients’ knowledge that are leading to the defect in diabetic nephropathy screening at one of the diabetes clinics. Methods: This cross-sectional hospital-based descriptive study was conducted at University charity teaching hospital affiliated to University of Medical Sciences and Technology (UMST) and covered 56 patients diagnosed with Diabetes Mellitus during the period from August to October 2013. Information was obtained by direct interviewing of patients using a questionnaire, and filled in the form of an interview. Results: A total of 56 patients were included, their mean age group was 60-69 and of them 51.8% were males. Regarding awareness about the symptoms of diabetic nephropathy, the most known symptom was fatigue, known by 27 (48.2%). Out of all the participants 55 (98.2%) reported checking their blood pressure regularly. A total of 50 (89.2%) believed that smoking had a harmful effect on their diabetes and 12 (21.4%) participants smoke cigarettes. Regarding exercise (54, 96.4%) believed that exercise is helpful in decreasing the incidence of diabetic nephropathy, however only 16 (28.6%) participants reported exercising regularly. A total of 51 (91%) have heard about the screening for diabetic nephropathy yet only 46 (82.1%) participant had their screening done regularly. Conclusion: Majority of participants had an understanding of the factors and knowledge on the signs of diabetic nephropathy, yet not all have evaded the risk factors. Raising awareness is essential but providing facilities to ensure its compliance is required. Keywords: Diabetes Mellitus; Nephropathy.